please solve the questions
Attachments:
![](https://hi-static.z-dn.net/files/dad/a8dadf3aabb11dfdd87ff405e2f96ca9.jpg)
Answers
Answered by
2
3-x^2/8+c^2 = -3/4
12-4x^2. = -24-3x^2
-12-3x^2+4x^2-12=0
x^2-36 =0
x^2=36
x =√36
x=6
12-4x^2. = -24-3x^2
-12-3x^2+4x^2-12=0
x^2-36 =0
x^2=36
x =√36
x=6
Answered by
3
x = 6. you just need to remove the square and solve it
sumit116:
hiii
Similar questions
Environmental Sciences,
9 months ago
English,
9 months ago
Science,
1 year ago
English,
1 year ago
English,
1 year ago